Intravenous Dabigatran Provides Adequate Anticoagulation for Cardiopulmonary Bypass Using a Rabbit Model. (23rd February 2023) - Nadtochiy, Sergiy M.; Stefanos, Tatsiana; Angona, Ronald E.; Darrow, Nathan; Jones, C.C.P., Karen; Feng, Changyong; Algahim, Mohamed; LeMoine, Dana; Westcott, Robin; Anderson, Brian; Swartz, Michael F.; Eaton, Michael P.
Abstract : Background: Heparin anticoagulation has been used successfully for cardiopulmonary bypass (CPB). However, an alternative anticoagulant approach is desirable due to the cases of heparin-induced thrombocytopenia. Dabigatran provides anticoagulation for an in vitro model of simulated CPB. The current analysis tests the hypothesis that dabigatran provides sufficient anticoagulation for CPB in intact rabbits. Methods: Nonlinear mixed effects models were used to estimate dabigatran parameters for a two-compartment pharmacokinetic model in 10 New Zealand White rabbits. A dabigatran infusion designed to maintain a plasma concentration of 90 µg/ml was run throughout CPB based on the pharmacokinetics. Animals were subjected to sternotomy and anticoagulated with IV dabigatran (six animals) or heparin (four animals). Rabbits were cannulated centrally using the right atrium and ascending aorta and CPB was maintained for 120 min. Measurement of activated clotting time, thromboelastometric reaction time, and blood gases were performed during CPB. Then, the animals were euthanized, and the brain and one kidney were removed for histology. Sections of the arterial filters were inspected using electron microscopy. Results: The observed dabigatran concentrations during CPB were greater than the target concentration, ranging from 137 ± 40 μg/ml at 5 min of CPB to 428 ± 150 μg/ml at 60 min, and 295 ± 35 μg/ml at 120 min. All rabbits completed 2 h of CPB without visible thrombosis. In the two groups, reaction time values were elevated, reaching 10, 262 ± 4, 198 s (dabigatran group) and 354 ± 141 s (heparin group) at 120 min of CPB. Brains and kidneys showed no evidence of thrombosis or ultrastructural damage. Sections of the arterial line filter showed minimal or no fibrin. There was no significant difference in outcomes between dabigatran- and heparin-treated animals. Conclusions: In this first-use, proof-of-concept study, the authors have shown that dabigatran provides acceptable anticoagulation similar to heparin to prevent thrombosis using a rabbit CPB model. Abstract : The hypothesis that dabigatran would provide sufficient anticoagulation for cardiopulmonary bypass was tested in a first-use, proof-of-concept study using a rabbit model of cardiopulmonary bypass that included a comparison group receiving heparin. The dabigatran loading dose and maintenance infusions were designed after first determining its pharmacokinetics in rabbits and the target concentration in an in vitro simulation of cardiopulmonary bypass. Dabigatran provided acceptable anticoagulation to prevent thrombosis during 2 h of cardiopulmonary bypass in rabbits that was similar to that provided by heparin and was well tolerated despite accumulating well above the target concentration during the period of anesthesia and cardiopulmonary bypass.